2020
DOI: 10.34117/bjdv6n3-335
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização físico-química e sensorial de biscoitos tipo cookie elaborados com farinha de berinjela (solanum melongena l.) E quiabo (abelmoschus esculentus l. Moench).

Abstract: A berinjela e o quiabo são vegetais amplamente conhecidos por seu valor nutricional e terapêutico. Na busca por alimentos com atividades funcionais, tem-se estudado a aplicação de farinhas vegetais no desenvolvimento de produtos, como biscoitos, no intuito de atrelar valor nutricional e sensorial. Diante disto, objetivou-se desenvolver e avaliar biscoitos tipo cookie elaborados com farinha de berinjela (Solanum melongena L.) e quiabo (Abelmoschus esculentus L. Moench). Tratou-se de uma pesquisa desenvolvida na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
3
0
4
Order By: Relevance
“…The partial substitution of wheat flour for okra flour has nutritionally enriched the product made by Rindiani and Kumalasari [ 34 ], increasing the amount of fiber, since okra flour has 14.21% fiber, while wheat flour has 2.7%. Brito et al [ 32 ] also produced a cake with okra flour and observed a good sensory acceptance of the product, contrary to what was observed by Oliveira et al [ 33 ], who did not obtain acceptable sensory characteristics in the developed product.…”
Section: Composition Cost and Main Uses Of Okramentioning
confidence: 89%
See 2 more Smart Citations
“…The partial substitution of wheat flour for okra flour has nutritionally enriched the product made by Rindiani and Kumalasari [ 34 ], increasing the amount of fiber, since okra flour has 14.21% fiber, while wheat flour has 2.7%. Brito et al [ 32 ] also produced a cake with okra flour and observed a good sensory acceptance of the product, contrary to what was observed by Oliveira et al [ 33 ], who did not obtain acceptable sensory characteristics in the developed product.…”
Section: Composition Cost and Main Uses Of Okramentioning
confidence: 89%
“…The influence of factors such as time and temperature on the yield or biological activity of the mucilage polysaccharides depends on the method used for the extraction. Ultrasound-assisted extraction showed excellent extraction yields (9–10%) at temperatures between 55 and 65 °C for 20 to 30 min [ 33 ].…”
Section: Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os ingredientes para a elaboração dos biscoitos de cenoura em diferentes farinhas foram adquiridos no comércio local da cidade de Campina Grande/PB. Foram elaboradas três formulações de biscoitos, biscoito CA com farinha de aveia; CT com farinha de trigo e CI com farinha integral, seguindo a metodologia proposta por Oliveira et al (2020), porém com algumas adaptações. Os materiais utilizados para produção dos biscoitos foram: açúcar, azeite, farinha de trigo, farinha de aveia, farinha integral, ovo, fermento e cenoura com casca, demonstrados na tabela 01.…”
Section: Elaboração Dos Biscoitos Adicionados De Cenoura Utilizando D...unclassified
“…Estudos já demostraram que o uso da farinha de berinjela (FB) como ingrediente em produtos como cookie (OLIVEIRA et al, 2020), pão (BARBOSA et al, 2019) e massas (OLIVEIRA et al, 2018) aumentou o teor de minerais (BARBOSA et al, 2019), proteína, lipídeo, carboidrato e fibras (OLIVEIRA et al, 2018), além de apresentar aceitação sensorial similar ao produto padrão (OLIVEIRA et al, 2020). Porém, níveis elevados de FB aumentaram Revista Vivências | Erechim | v. 19 | n. 38 | p. 43-55 | jan./jun.…”
Section: Introductionunclassified